Pericoronary adipose tissue attenuation is associated with non-calcified plaque burden in patients with chronic coronary syndromes - Giesen, Alexander; Mouselimis, Dimitrios; Weichsel, Loris; Giannopoulos, Andreas A.; Schmermund, Axel; Nunninger, Maximilian Martin; Schütz, Moritz; André, Florian; Frey, Norbert; Korosoglou, Grigorios (Journal of cardiovascular computed tomography, 2023)
Background - Pericoronary adipose tissue attenuation (PCAT) is a marker of inflammation of the pericoronary fat tissue, which can be assessed by coronary computed tomography angiography (CCTA). Its prognostic value was reported in previous studies. Nevertheless, the relationship between PCAT, plaque burden and coronary artery disease (CAD) severity, are not well defined. - Aim - We sought to evaluate the relationship between PCAT, CAD severity based on the CAD-RADS 2.0 score and plaque burden in patients with chronic coronary syndrome (CCS). - Methods - Consecutive patients with a clinical indication for CCTA due to suspected or known CCS were included in our study. PCAT was measured in the proximal 4 ​cm of each of the right coronary artery (RCA), left anterior descending artery (LAD), and the left circumflex artery (LCX). The CAD-RADS 2.0 score was assessed in all patients and total, calcified, and non-calcified plaque burden was quantitatively measured. - Results - 868 patients (median age of 67.0 (IQR ​= ​58.0-75.0)yrs., 400 (46.1%) female) underwent CCTA between September 2020 and August 2022 due to CCS. Weak correlations were found between PCAT and the total plaque burden, as well as with the Agatston score, whereas no correlations were found between PCAT and CAD-RADS 2.0 score. Associations were also observed between the PCAT of the LAD, RCA and LCX with non-calcified plaque burden (Odds ratios of 1.22 (95%CI ​= ​1.15-1.29), 1.11 (95%CI ​= ​1.07-1.17) and 1.14 (95%CI ​= ​1.08-1.14), respectively, p ​< ​0.001 for all) which were independent of age, the Agatston score, and the CAD-RADS 2.0 score). In addition, higher PCAT were noticed with increasing number of plaques, exhibiting high-risk features per patient (p ​< ​0.05 by ANOVA for all). - Conclusion - PCAT exhibits significant associations with non-calcified plaque burden and plaques with high-risk features in patients undergoing CCTA for CCS. Thus, PCAT may identify high-risk patients who could benefit from more aggressive preventive therapy, which merits further investigation in future studies.